Study on formability and strain hardening index: influence of particle size of boron carbide (B4C) in magnesium matrix composites fabricated by powder metallurgy technique. (27th January 2020) - Rajkumar, P R; Kailasanathan, C; Senthilkumar, A; Selvakumar, N; JohnRajan, A
Abstract: In the present investigation, Magnesium composites have been fabricated with boron carbide (B4 C) as reinforcement by powder metallurgicaltechnique. Two different particle sizes—micro and nano B4 C particles with weight percentage of 0%, 5% and 10% has been studied. The green compacts were prepared by cold pressing and then sintering the specimens before being subjected to cold upsetting under triaxial stress state condition in order to study the phenomenon of workability and instantaneous strain hardening index. Powder characterizations are discussed using x-ray Diffraction peaks, Scanning Electron Microscope images and Energy Dispersive Spectrum analysis. Cold upsetting has been preferred to investigate the performance of the composites. The values of formability stress index factor ( β σ ), various stress ratio ( σ θ / σ eff, σ m / σ eff and σ z / σ m ) parameters and instantaneous strain hardening index ( n i ) are observed for increase in % of B4 C particles and its sizes. The experimental results were analyzed pertaining to relative density. The results reveal that Mg-10% nano B4 C composite has higher relative density, formability stress index factor and hence high workability than the other composites. The addition of B4 C particles as reinforcement affects the strain hardening index due to geometric and work hardening of the composites.